"The Higher You Fly, the Further You Fall": White-Collar Criminals, "Special Sensitivity" and the Impact of Conviction in the United Kingdom. Issue 5 (4th July 2018) - Button, Mark; Shepherd, David; Blackbourn, Dean
ABSTRACT: The resilience of some high-profile white-collar criminals in the media gaze after prison may lead some to conclude, particularly as some research also supports this notion, that this group of offenders generally manages well after conviction. Research in this area is, however, small and largely American. The authors seek to add to this small body of research by offering findings on the impact of conviction on 17 UK convicted white-collar criminals after completion of their sentence. It provides a unique insight into the consequences of conviction, showing that although there were some offenders who did experience limited impact and coped well, there was also a significant group who suffered a decline in status, financial losses, negative media coverage, and relationship and mental health problems, to name some. The authors argue more research is needed on this group and their needs as they are often neglected by the criminal justice system.